2017
DOI: 10.1097/gox.0000000000001231
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related Risk Factors in Implant-based Breast Reconstruction Using AlloDerm

Abstract: With a population in which 70% of the patients were overweight or obese, we reviewed retrospectively 135 breasts of 70 consecutive patients who underwent implant-based immediate breast reconstruction using freeze-dried AlloDerm as the acellular dermal matrix. Several obesity-related parameters were evaluated to determine their possible correlation to early postoperative complications. We found that breast width and surface area of AlloDerm usage correlated with the development of infection and mastectomy skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…In contrast, higher BMI and active tobacco use were found to be associated with a greater risk of infection and reconstructive failure. This is not surprising in light of previous reports demonstrating the unfavorable impact of these comorbidities on postoperative outcomes following implant‐based breast reconstruction 27,28 . Additionally, adjuvant chemotherapy was noted to increase the risk of infection in this study, validating the findings of Peled et al 29 …”
Section: Discussionsupporting
confidence: 91%
“…In contrast, higher BMI and active tobacco use were found to be associated with a greater risk of infection and reconstructive failure. This is not surprising in light of previous reports demonstrating the unfavorable impact of these comorbidities on postoperative outcomes following implant‐based breast reconstruction 27,28 . Additionally, adjuvant chemotherapy was noted to increase the risk of infection in this study, validating the findings of Peled et al 29 …”
Section: Discussionsupporting
confidence: 91%
“…In addition, this particular population poses a challenge due to longer operative time and technical difficulties [74]. Our findings comply with previous studies on the association between obesity and increased risk of postoperative complications, including seroma, infection and reconstructive failure [32,74,75,76,77]. In addition, our analysis showed that the odds of complications increased 8.1% for each unit increase in a patient’s BMI.…”
Section: Discussionsupporting
confidence: 91%
“…Patient factors are well understood and are important for patient counseling before surgery. 34,35 One of the covariates that has previously been discussed in other studies, diabetes, showed to be a significant factor in our univariate analysis in the rates of complication to occur, specifically breast wounds. Diabetes is noted to have a lack of association in causing complications from previous studies, which is believed to have minimal contribution to flap perfusion.…”
Section: Logistic Regression Analysismentioning
confidence: 74%